BONE MINERAL DENSITY IN PHYSIOTHERAPISTS: The association of osteoporosis with occupational exposure to non-ionizing radiation modalities - Güneş Yavuzer,; Birkan Sonel,; Gülay Dinçer,; Tansu Arasıl, (Archives of Rheumatology, 2002)
The aim of this study was to determine whether bone mineral density of physiotherapists (PT) is lower than expected, and to investigate the association with the duration of exposure to non-ionizing radiation modalities. Forty PTs who have been operating physical modalities for at least one year and forty control subjects who had no history of exposure to non-ionizing radiation modalities were included the study. Risk factors of osteoporosis were assessed by a detailed questionnaire. Duration of exposure to non-ionizing radiation modalities (shortwave or microwave diathermy, ultrasound, infrared, ultraviolet lamps and laser) was recorded. Stiffness index and z-scores were measured using a Lunar Achiles Expres ultrasound densitometer. In PTs, stiffness was 11% and z-score was 22% lower than the control group, however, the difference was not statistically significant (p>0.05). The average duration of exposure to non-ionizing radiation modalities was 12.4 ± 6.8 years. The relationship between bone density and the duration to radiation modalities was not statistically significant (p>0.05). In conclusion physiotherapists are unlikely to have an extra risk for osteoporosis after being exposed to non-ionizing radiation.